SpectrumChain: a disruptive dynamic spectrum-sharing framework for 6G - Wu, Qihui; Wang, Wei; Li, Zuguang; Zhou, Bo; Huang, Yang; Wang, Xianbin (Science China. Information sciences, 2023)
The sixth-generation (6G) wireless network will support ubiquitous connectivity and diversified scenarios to satisfy the requirements of various emerging applications. Full spectrum is a key enabler for 6G to achieve the ambitious goal of a Tbps-scale data rate. In this paper, we first review the scenario and potential spectrum plan for 6G and then focus on SpectrumChain, a blockchain-based dynamic spectrum-sharing (DSS) framework for 6G. The unique characteristics of blockchain for DSS are presented along with key technologies. Finally, the conclusion and future development trends are discussed.